Characterization of the reaction environment in flow reactors fitted with BDD electrodes for use in electrochemical advanced oxidation processes: A critical review. (20th January 2020) - Cornejo, Oscar M.; Murrieta, María F.; Castañeda, Locksley F.; Nava, José L.
Abstract: The study of electrochemical advanced oxidation processes (EAOPs) requires electrochemical reactors that can ensure a controlled flow and use of a wide range of boron-doped diamond (BDD) electrode shapes, before the development and scaling-up of these processes. BDD electrodes are classified as non-active electrodes, and the convenience of their use is attributed to their high capacity for producing adsorbed hydroxyl radicals BDD (OH) from water discharge, which allows the anodic oxidation (AO) of persistent organic pollutants (POPs). These electrodes have also been used in other EAOPs, such as electro-Fenton (EF), photoelectro-Fenton (PEF), and solar photoelectro-Fenton (SPEF) processes. Many research groups have employed BDD plates (2D electrodes) and meshes (3D porous electrodes) in filter-press type electrolyzers, and Raschig ring-shaped BDD electrodes in trickle tower reactors, to determine the characteristics of flow dispersion, mass transport, and current distribution (the reaction environment) in fundamental investigations and environmental applications. Several papers have dealt with the experimental characterization of the reaction environment, because it determines the space-time yield, conversion, mineralization current efficiencies, and electrolytic energy consumption during the degradation of POPs, although its mathematical modeling is rather scarce. This critical review focuses on the characteristics of different flow reactors using BDD electrodes and carries out a rigorous analysis of the reaction environment in such reactors. Studies include the effect of electrolyte velocity on the flow dispersion, mass transport rate, and current distribution. Highlights: Boron-doped diamond (BDD) electrodes fitted in electrochemical flow reactors. Plates, meshes and Raschig ring BDD electrodes in filter-press and trickle tower cells. Degradation of organics by anodic oxidation, electro-Fenton and photoelectro-Fenton. Characterization of the flow dispersion, mass transport and current distribution. CFD simulations allow identifying non-ideal flow behavior to prevent and correct it.